The impact of free trade agreements (FTAs) on business in the Republic of Korea - Inkyo Cheong; Jungran Cho (Asian Development Bank Institute (ADBI), 2009)
The Republic of Korea (hereafter Korea) continues to promote an open-trade system via the conclusion of free trade agreements (FTAs), arguing that Korean enterprises will obtain considerable business opportunities under the FTAs the government has implemented. However, the FTAs that are currently being implemented in Korea are said to be beneficial only to some enterprises. This study presents new evidence from a survey conducted from July-August 2008 on 120 Korean firms. The paper explores critical questions regarding the utilization of FTAs, their perceived costs and benefits, perceptions of multiple rules of origin (ROOs), and policy and institutional support mechanisms for FTAs. One of the key findings is that most of the currently implemented FTAs in Korea were concluded with small- and medium-sized developing countries. Moreover, within these FTAs, the range of preferential tariffs is not very broad in scope; as such, only one out of five enterprises was found to be utilizing them. However, since the conclusion of FTAs with the United States and the European Union, Korean businesses have become very interested in utilizing those respective FTAs. The government should make efforts for early implementation of these FTAs. In the FTAs concluded by Korea, ROOs are strict and complicated. In future FTAs, a more neutral and lenient form of ROOs should be adopted.
Keywords: F15; F13; 330